TINGKAT PENGETAHUAN, SIKAP DAN KETERAMPILAN KELUARGA TENTANG PERAWATAN PADA PENDERITA TB PARU : STUDI DESKRIPTIF - Beatris Palele; Valen Fridolin Simak; Septriani Renteng (JURNAL KEPERAWATAN, 2022)
Abstract: Background. The importance of knowledge, attitudes and skills of families with pulmonary TB patients in caring for sick family members in supporting the treatment process on a regular basis so that treatment can be successful. The purpose of this study was to describe the level of knowledge, attitudes and skills of families about care for patients with pulmonary TB in 7 working areas of the Talaud Islands District Health Center. This Study used descriptive/survey methods, the sample in this study amounted to 80 respondents obtained through random sampling that met the inclusion criteria. The results showed that family knowledge was in the sufficient category (50.0%), family attitudes were in the sufficient category (55%) and most family skills were in the sufficient category (62.5%). The conclusion is that the characteristics and levels of knowledge, attitudes and skills of families about care for patients with pulmonary TB in 7 working areas of the Talaud Islands District Health Center. Suggestions The importance of support and encouragement from families of patients with pulmonary TB in caring for sick family members in terms of reminding families to take medicine, reminding them to always wear masks, preparing for sufferers' needs and even being more active in taking patients for control to health services on a regular basisÂ Keywords: Knowledge Level; Family Attitude; Family Skills; Tuberculosis